1976
DOI: 10.1055/s-0028-1095599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Changes in Serum Calcium on Glucose Tolerance, Blood Glucose, IRI and Cortisol Levels

Abstract: 151According to experimental data calcium ions are involved both in the secretory process (Grodsky and Bennett 1966, Mi/ner and Haies 1967, Malaisse and Malaisse-Lagae 1970_and the action of imulin (Kissebah, Hope-Gill, Vydelingum, Tulloch, Garke and Fraser 1975). Since only a few cJinicai observations have been reported on this subject so far, it seemed worthwhile to investigate the effect of an altered serum calcium on glucose tolerance, blood glucose and IRI levels. Materials and Methods11 diabetics -trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1977
1977
1983
1983

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Similar findings have been reported by Rizvi et normal glucose disappearence and insulin secretion in azotaemic, hypocalcaemic subjects, and in a subgroup of their patients insulin secretion was even reduced by calcium infusion [14]. In our earlier study the insulin response to oral glucose load in chronically hypocalcaemic patients was normal and unaffected by calcium injection [3]. Recently Harter has demonstrated that in Parathyroid hormone-treated dogs glucose-stimulated insulin release was increased by hypophosphataemia, but not by hypercalcaemia.…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings have been reported by Rizvi et normal glucose disappearence and insulin secretion in azotaemic, hypocalcaemic subjects, and in a subgroup of their patients insulin secretion was even reduced by calcium infusion [14]. In our earlier study the insulin response to oral glucose load in chronically hypocalcaemic patients was normal and unaffected by calcium injection [3]. Recently Harter has demonstrated that in Parathyroid hormone-treated dogs glucose-stimulated insulin release was increased by hypophosphataemia, but not by hypercalcaemia.…”
Section: Discussionsupporting
confidence: 87%
“…glibenclamide (Gero et al, 1977) whereas hypocalcaemia has been associated with decreased insulin responses to glucose (Yasuda et al, 1975;Rizvi et al, 1975) and arginine (Laron & Rosenberg, 1970). On the other hand, reports by other investigators have not found this positive correlation of serum calcium levels and insulin responses (Lisch e l al., 1973;Gero et al, 1976). The explanation for these contradictions are not apparent at the moment.…”
Section: Discussionmentioning
confidence: 91%
“…Maximum blood sugar level (Max BS), maximum serum IRI (Max IRI), maximum rise of blood sugar level from the fasting state (Max dBS), maximum rise of serum IRI from the fastine level (Max JIRI). maximum levels without a significant change in serum IRI (Gero et al, 1976). In patients with islet cell tumor, intravenous calcium infusion caused a release of insulin and proinsulin, but no such effect was obtained in normal subjects (Gaeke et al, 1975).…”
Section: Methodsmentioning
confidence: 93%